The Effectiveness of Audio-Visual Media on the Recognition of Hijaiyah Letters through Singing in Early Childhood 5-6 Years in PAUD Al-Fiqihiyah - S. Kutanga, Nurul Aini; Nurhayati, Nurhayati; Amrullah, Amrullah; Durrotunnisa, Durrotunnisa (Journal of Educational Sciences, 2025)
The introduction of hijaiyah letters to children should be done in an attention-grabbing way. The main focus of the introduction of hijaiyah letters in this study is the difficulties faced by children in recognizing hijaiyah letters, children's inability to pronounce hijaiyah letters, and their inability to bolster hijaiyah letters. The researcher used learning media such as audio-visual media, hijaiyah letter cards and the task of bolstering hijaiyah letters. The purpose of this study is to test the effectiveness of audio-visual media on the recognition of hijaiyah letters through singing in early childhood 5-6 years old at PAUD Al-Fiqihiyah Palu. The method used in this study is a quantitative approach with a descriptive approach. Data were collected through observation, interviews, documentation, and research instruments. The results of the analysis showed that the t-value reached 19,697 > table 1,761, with a significance level of 0.001. Given the significance obtained of less than <0.05, it can be concluded that H0 is rejected and the hypothesis H1 is accepted, which shows the effectiveness of audio-visual media on the recognition of hijaiyah letters.